Estimation of adhesive friction of the molten polymer by flow through a capillary rheometer - Piszczek, K.; Skórczewska, K.; Sterzyński, T. (Polimery, 2009)
The possibilities to estimate adhesive friction (Ta), which is a constituent of friction force, during polymer flow by the use of capillary piston rheometer were analyzed. The linear dependence between Ta constituent and the height of polymer material column in capillary rheometer (h) was applied to determine the coefficient of adhesive friction (...). It was found that ... value, first of all, depends on the load imposed (P), whereas temperature within the range studied had no effect on its value.